THE IMPORTANCE OF MODERN TECHNOLOGIES IN THE DEVELOPMENT OF PUBLIC SPORTS AND PHYSICAL EDUCATION LESSONS - Ahmedjanov Shuhrat Boltayevich; Bahrullayev Mamur (Galaxy International Interdisciplinary Research Journal, 2023)
This article talks about innovative technologies for the development of mass sports. Today, innovative technologies are an integral part of any human activity. Physical education and sports are no exception. In modern conditions, innovative technologies help to improve physical results, create comfort for sports, as well as the effectiveness of physical exercises.